2015
DOI: 10.2146/ajhp150080
|View full text |Cite
|
Sign up to set email alerts
|

Independent prescribing by hospital pharmacists: Patterns and practices in a Canadian province

Abstract: The survey results indicated that, in an average week, hospital pharmacists with APA prescribed for almost half of the patients they cared for as part of the interdisciplinary team. Prescribing most frequently occurred after team discussion and most often involved adjusting dosages based on organ function and clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Building harmonious relationships with health professionals is key to the implementation of PP . Supporting this, Canadian pharmacists were more likely to prescribe after interdisciplinary team discussions . This resonates with research studying the redistribution of occupational power and related improved coordination of healthcare teams, where a key component of collaboration is described as the ‘relative autonomy of clinicians over their scope of practice to deliver patient care’, requiring a shared understanding of roles .…”
Section: Discussionmentioning
confidence: 72%
“…Building harmonious relationships with health professionals is key to the implementation of PP . Supporting this, Canadian pharmacists were more likely to prescribe after interdisciplinary team discussions . This resonates with research studying the redistribution of occupational power and related improved coordination of healthcare teams, where a key component of collaboration is described as the ‘relative autonomy of clinicians over their scope of practice to deliver patient care’, requiring a shared understanding of roles .…”
Section: Discussionmentioning
confidence: 72%
“…This finding contrasts with the previous survey of hospital pharmacists in Alberta where APA was used most frequently to adjust medication dosages and for medication reconciliation. 21 However, neither this study nor the previous asked pharmacists to describe the degree of involvement they have in each clinical activity. Although 100% of oncology pharmacists with APA are involved with medication reconciliation, the degree of involvement they have and their established role among the multidisciplinary team in their practice may influence how useful prescribing is for this particular activity.…”
Section: Discussionmentioning
confidence: 88%
“…In 2014, a web-based survey was done to determine the prescribing frequency of hospital pharmacists in Alberta with APA. 21 Although it was not restricted to oncology pharmacists, it captured information applicable to pharmacists with APA in Alberta. They found that the majority of hospital pharmacists practiced in acute care and inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alberta was the first province in Canada to approve independent prescribing for pharmacists. 59 We are seeing extended services such as drug ordering and monitoring by clinical pharmacist practitioners in ICUs in the United States. 14 The role of the pharmacist as an independent prescriber is becoming a reality and will likely continue to grow, which may result in improved prescribing with better accuracy.…”
Section: Pharmacist Prescribingmentioning
confidence: 99%